Profiles of perfectionism, parental climate, and burnout among competitive junior athletes - Gustafsson, H.; Hill, A. P.; Stenling, A.; Wagnsson, S. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Recent research suggests that groups of athletes which differ in terms of perfectionism and perceptions of achievement climate can be identified. Moreover, these groups also differ in terms of burnout symptoms. The purpose of the current study was to extend this research by examining whether discernible groups can be identified based on scores of perfectionism and perceptions of parent-initiated climate and, then, whether these groups differ in terms of burnout. Two-hundred and thirty-seven Swedish junior athletes (124 males and 113 females aged 16-19) from a variety of sports completed measures of athlete burnout, multidimensional perfectionism, and parent-initiated motivational climate. Latent profile analysis identified four groups: non-perfectionistic athletes in a task-involving climate, moderately perfectionistic athletes in a task-involving climate, highly perfectionistic athletes in a task-involving climate, and highly perfectionistic athletes in a mixed climate. The latter two groups reported higher levels of burnout in comparison to other groups. The findings suggest that junior athletes high in perfectionism may be at comparatively greater risk to burnout and that this may especially be the case when they perceive their parents to emphasize concerns about failure and winning without trying one's best.